The Third World Queer - Benedicto, Bobby (Archīum Ateneo, 2013)
As queerness becomes a mechanism for exclusions, queerness becomes the site of an ethical struggle over who will reap the rights and benefits of normativity. who will incur the costs of non-normativity, a struggle that ties economic and institutional enfranchisement. With the admission of women and people of color into predominantly white academic settings, the economic character of the American academy did not simply vanish. In reality its economic system and thus its political policy is directed from outside. For Stuart Hall liberatory movements were both political and epistemological formations that attempted to simultaneously disinter and reconstruct subjugated histories around race, gender, and nation. The disinternment and reconstruction of those histories put certain social pressures on canonical forms of history. In his classic essay "The Local and the Global", Stuart Hall locates the social movements within the emergence of a new trajectory for global capitalism.